Parry Romberg syndrome: a case report (Bangladesh Journal of Medical Science, 2015)
Parry Romberg syndrome is a rare neurocutaneous disorder of unknown etiology characterized by facial hemiatrophy of fat, skin, connective tissue and MRI changes in the brain. Here we report a 30 years old woman who presented with facial hemiatrophy, headache and facial pain, hemi-masticatory spasm, atrophy of tongue, temporal hemianopia and hyperintense lesions on MRI.Bangladesh Journal of Medical Science Vol.14(3) 2015 p.308-309